Engineering Saccharomyces cerevisiae for geranylgeraniol overproduction by combinatorial design. Issue 1 (December 2017) - Song, Tian-Qing; Ding, Ming-Zhu; Zhai, Fang; Liu, Duo; Liu, Hong; Xiao, Wen-Hai; Yuan, Ying-Jin
Abstract Combinatorial design is an effective strategy to acquire the optimal solution in complex systems. In this study, the combined effects of pathway combination, promoters' strength fine-tuning, copy numbers and integration locus variations caused by δ-integration were explored inSaccharomyces cerevisiae using geranylgeraniol (GGOH) production as an example. Two GGOH biosynthetic pathway branches were constructed. In branch 1, GGOH was converted from isopentenyl pyrophosphate (IPP) and farnesyl diphosphate (FPP). In branch 2, GGOH was derived directly from IPP and dimethylallyl pyrophosphate (DMAPP). Regulated by 10 combinations of 11 diverse promoters, a fusion geneBTS1-ERG20, a heterologous geranylgeranyl diphosphate synthase fromSulfolobus acidocaldarius (GGPPSsa ) and an endogenous N-terminal truncated gene 3-hydroxyl-3-methylglutaryl-CoA reductase isoenzyme 1 (tHMGR ), were incorporated into yeast by δ-integration, leading to a series of GGOH producing strains with yields ranging from 18.45 mg/L to 161.82 mg/L. The yield was further increased to 437.52 mg/L by optimizing the fermentation medium. Consequently, the GGOH yield reached 1315.44 mg/L in a 5-L fermenter under carbon restriction strategy. Our study not only opens large opportunities for downstream diterpenes overproductions, but also demonstrates that pathway optimization based on combinatorial design is a promising strategy to engineer microbes for overproducing natural products with complex structure.